Figury samotnej żałoby - Kaczmarek, Agnieszka (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
The intention of the author of this paper is to juxtapose the image of mourning that accompanies the experience of death as represented in Blue, a film directed by Krzysztof Kieślowski, as a part of a The Three Colors Trilogy, and its personal linguistic expression in The Mourning Diary by Ronald Barthes. Both figures of mourning render to us an intimate world of mourning linked to a loss of somebody dear and express a peculiar state of exclusion as well as various yet real images of mourning “at work”. In both Blue and The Mourning Diary we are exposed to a different rhythm of life closely linked to the melancholy of loss and a resultant vulnerability of the mourner towards the world.